Ingredients to prepare one (or several) story(s) of the puppet theater (Móin-Móin Magazine - Studies in the Art of Puppetry, 2023)
Puppets "exist" beyond stage: they are objects of material culture and this pre and post-theatrical existence leads us to wonder about their presence in the archives. In this work I aim to reflect on the ingredients to prepare one (or several) history(ies) of puppet theater: what are the materials available (or not) at the moment of reconstructing shows and experiences with puppets. Documents from institutional archives and personal archives have been privileged reservoirs in this task. However, the puppet, as a staging protagonist, can offer us some clues about the show, the creative process and the work of a group or artist.
Keywords: puppet; historiography; archive; document; material culture